Application of gas chromatography-mass spectrometry and elemental analyzer-isotope ratio mass spectrometry techniques to distinguish lard from selected animal fats before and after chemical glycerolysis - Ahmad Nizar, Nina Naquiah (2013)
A study was conducted to differentiate lard from selected animal fats namely chicken fat, beef fat and mutton fat, before and after chemical glycerolysis. It was carried out using Gas Chromatography Mass Spectrometry (GCMS) and Elemental Analyzer–Isotope Ratio Mass Spectrometry (EA-IRMS) techniques. The comparison of overall fatty acid data obtained by Gas Chromatography analysis before and after chemical glycerolysis showed that lard and chicken fats shared common characteristics by having palmitic, oleic and linoleic acids as major fatty acids. On the other hand, beef and mutton fats shared common characteristics by possessing palmitic, stearic and oleic acid as major fatty acids. Direct comparisons among the fatty acid data therefore may not be suitable for differentiation of animal fats. When the fatty acid distributional data of the animal fats was subjected to Principle Component Analysis (PCA), it was demonstrated that stearic, oleic and linoleic acids were the most discriminating parameters in the clustering of animal fats to four subclasses. The stable isotope analysis of lard and selected animal fats before chemical glycerolysis using EA-IRMS showed significant difference in the carbon isotope ratios (δ13C). The same finding was observed after chemical glycerolysis. This would be a good indicator in discrimination of lard, chicken, beef and mutton fats. The current finding leads to a more efficient method, to screen and ascertain the source of origin of fats used in food products.